2012
DOI: 10.1111/j.1365-2966.2012.21341.x
|View full text |Cite
|
Sign up to set email alerts
|

On the HU Aquarii planetary system hypothesis

Abstract: In this work, we investigate the eclipse timing of the polar binary HU Aquarii that has been observed for almost two decades. Recently, Qian et al. attributed large (O-C) deviations between the eclipse ephemeris and observations to a compact system of two massive jovian companions. We improve the Keplerian, kinematic model of the Light Travel Time (LTT) effect and re-analyse the whole currently available data set. We add almost 60 new, yet unpublished, mostly precision light curves obtained using the time high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(134 citation statements)
references
References 41 publications
2
130
2
Order By: Relevance
“…They speculate about other mechanisms being responsible for the observed variations, such as changes in the shape of the secondary star due to dynamo effect. However, in a very recent work, Goździewski et al (2012) publish almost 60 new eclipse egress times with better accuracy. Combining these with reanalyzed previous data, the authors find that a single circumbinary companion gives the best explanation for the O−C curve.…”
Section: A2 Eclipsing Wd+ms Pcebsmentioning
confidence: 99%
“…They speculate about other mechanisms being responsible for the observed variations, such as changes in the shape of the secondary star due to dynamo effect. However, in a very recent work, Goździewski et al (2012) publish almost 60 new eclipse egress times with better accuracy. Combining these with reanalyzed previous data, the authors find that a single circumbinary companion gives the best explanation for the O−C curve.…”
Section: A2 Eclipsing Wd+ms Pcebsmentioning
confidence: 99%
“…The question of long-term stability of such planetary systems then arises, and it may not be easy (or even impossible) to find a configuration which is compatible with observations and at the same time ensures the survival of the planetary system on secular timescales. Examples are HU Aqr (Qian et al 2011;Horner et al 2011;Goździewski et al 2012;Wittenmyer et al 2012); NN Ser Brinkworth et al 2006;Beuermann et al 2010;Hessman et al 2011;Marsh et al 2014) and HW Vir (Lee et al 2009;Beuermann et al 2012b;Horner et al 2012).…”
Section: The Cyclic Period Variationsmentioning
confidence: 99%
“…An updated version was published by Pilarčík et al (2012), who also included some post-common envelope binaries (PCEBs) with similar period variations. HU Aqr (Qian et al 2011;Goździewski et al 2012) and RR Cae (Qian et al 2012) may be added to this list.…”
Section: The Cyclic Period Variationsmentioning
confidence: 99%
“…Horner et al (2012b)) we found that the formal parameter errors as obtained from the best-fit co-variance matrix are too optimistic. We therefore determined parameter errors from Monte Carlo bootstrap experiments (Goździewski et al 2012). For each bootstrap dataset we used the best-fit model as our initial guess and recorded the resulting parameters.…”
Section: Least-squares Fitting and Parameter Uncertaintiesmentioning
confidence: 99%
“…The proposed companions around HU Aqr have been studied in detail, and a series of studies have revealed them to be dynamically unfeasible (Horner et al 2011;Hinse et al 2012a;Wittenmyer et al 2012a;Funk et al 2011Funk et al , 2012Goździewski et al 2012). The same is true of HW Vir ) and NSVS 14256825 Hinse et al 2014).…”
Section: Introductionmentioning
confidence: 99%